Financial and legal aspects of innovation clusters - A. S. Kirpa (Гуманитарные и юридические исследования)
The purpose of this article is to study the issues of legislative regulation of innovation clusters in the system of financial and tax law. Some aspects of the problems in the field of tax incentives for innovation clusters are studied. The priority goal of the study is to conduct an up-to-date analysis of legislative trends that accompany innovation clusters. The study contributes to the formation of approaches to the value, effectiveness and targeting of financial and legal incentives that affect the development of innovation clusters.At the same time, the authors proceeded from an interdisciplinary approach, since the problem of the legal status of innovation clusters inevitably affects the subject of regulation of various branches of law and has both constitutional and legal, financial, legal, civil, administrative and other aspects.For the most correct and uniform understanding of the elements of the social relations under consideration, the authors pay attention to the categorical and conceptual apparatus, which reflects intersectoral relations and the dual legal nature of the studied relations arising from the functioning of innovative clusters. Generalization and systematization of the main directions, trends of state policy on the development of legal regulation of innovation clusters made it possible to reveal the relevance and importance of financial support from public authorities as an incentive for innovative development of the economy.The interaction of sciences significantly increases the effectiveness of financial and legal research. Innovation clusters are also considered in the context of the relationship between law and economics. Only interdisciplinary approaches with indisputable consideration of foreign legislative experience, including law enforcement practice, should be the basis for scientific and legal understanding of the legal status of innovation clusters, stimulating the activity of innovation clusters as locomotives of the modern economy, developing financial and legal instruments that contribute to the effective implementation of cluster policy in the modern world. legal field.The conducted analysis of publications shows the absence of scientific monographic studies devoted to the study of the financial and legal nature of innovation clusters. The author believes that in the modern conditions of the development of the digital economy, which creates new challenges for innovation, the study of the financial and legal essence of innovation clusters is important and timely. For the most correct and uniform understanding of the elements of the social relations under consideration, the authors pay attention to the categorical and conceptual apparatus, which reflects intersectoral relations and the dual legal nature of the studied relations arising from the functioning of innovative clusters. Generalization and systematization of the main directions, trends of state policy on the development of legal regulation of innovation clusters made it possible to reveal the relevance and importance of financial support from public authorities as an incentive for innovative development of the economy.The article also notes the underdevelopment of the legislative and legal field of economic clustering and the negative impact of the legislative factor on its full development. Legislation in the field of innovation (clustering) is not systemic, it is dominated by numerous disparate by-laws, including those at the regional level.Much attention is paid by the author to the financial and legal essence and nature of innovative clusters as an organizational and legal form of attracting investments. The financial and legal essence of innovation clusters is determined by the following important factors. The legal regulation of investment clusters covers wide areas of the country’s public life and is part of the general financial and legal regulation of cash flows – investments that are included in the financial system of the state. Innovation clusters attract investments, which are one of the backbone categories of financial law. The main areas of financial and legal regulation of investment clusters also include the budget vector, which is realized through the effectiveness of the state as an investor through budget allocations. Obviously, the tax regulation of innovation clusters is characterized by an incentive-stimulating and mobilization orientation. The practical experience of the application of legislation in the area under consideration, as well as the most effective methods of stimulating innovation clusters are studied. The study was carried out on the basis of general scientific interdisciplinary and specific methods (formal-legal, comparative-legal, structural-functional).